2008
DOI: 10.1154/1.2960860
|View full text |Cite
|
Sign up to set email alerts
|

X-ray powder diffraction study of Sn0.59Ti0.41Te3O8

Abstract: The crystal structure of titanium-tin tellurium oxide Sn 0.59 Ti 0.41 Te 3 O 8 has been determined using X-ray powder diffraction techniques. At room temperature, the title compound crystallizes in cubic space group Ia-3, with lattice parameter a = 11.05515͑6͒ Å. Rietveld refinement of the structure led to final confidence factors R p = 0.0395 and R wp = 0.0577. The structure of Sn 0.59 Ti 0.41 Te 3 O 8 consists of isolated Ti/ SnO 6 -octahedra slightly deformed in the a direction. The TeO 4 E ͓E = lone pair o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In subsequent studies, crystal-structure refinements on the basis of single-crystal X-ray data were reported for the mineral winstanleyite with composition (Ti 0.96 Fe 0.04 )Te 3 O 8 (Bindi & Cipriani, 2003), and for the synthetic compound ZrTe 3 O 8 (Noguera et al, 2003;Lu et al, 2019). A powder X-ray study of the solid solution Sn 0.59 Ti 0.41 Te 3 O 8 crystallizing in the M IV Te 3 O 8 structure type has also been reported (Ben Aribia et al, 2008).…”
Section: Chemical Contextmentioning
confidence: 97%
“…In subsequent studies, crystal-structure refinements on the basis of single-crystal X-ray data were reported for the mineral winstanleyite with composition (Ti 0.96 Fe 0.04 )Te 3 O 8 (Bindi & Cipriani, 2003), and for the synthetic compound ZrTe 3 O 8 (Noguera et al, 2003;Lu et al, 2019). A powder X-ray study of the solid solution Sn 0.59 Ti 0.41 Te 3 O 8 crystallizing in the M IV Te 3 O 8 structure type has also been reported (Ben Aribia et al, 2008).…”
Section: Chemical Contextmentioning
confidence: 97%